Peran Sanro Pammana dalam Sistem Kesehatan Tradisional Masyarakat Bugis: Studi Kasus Ritual Kelahiran dan Perawatan Ibu dan Bayi - Anjarsari, Hilda; Muzakkir, Abd. Kahar; Badollahi, Muh. Zainuddin; Busro, Busro (SIGn Journal of Social Science, 2024)
This research aims to examine the role of the Sanro Pammana within the traditional healthcare system of the Bugis People, particularly about birth rituals and maternal and infant care, as well as to identify the challenges they face amidst the currents of modernization. Employing a qualitative approach and ethnographic methods, data were collected through participant observation, in-depth interviews, and document analysis in Sanrobone and Bila Villages, Bone Regency, South Sulawesi. Data analysis was conducted inductively to describe and understand the observed phenomena. The findings reveal that the Sanro Pammana plays an essential role in the maternal and neonatal health of the Bugis community, serving as a central figure who possesses profound local knowledge and wisdom regarding pregnancy, childbirth, and postpartum care. The traditional healthcare practices performed, including the ma’cerra wettang and mappassili rituals, reflect the holistic worldview of the Bugis People, integrating physical, spiritual, and socio-cultural dimensions. Trust in the Sanro Pammana is deeply rooted in tradition and positive community experiences. However, their existence is currently challenged by the forces of modernization, such as shifting preferences towards modern healthcare services, limited regeneration, a lack of formal recognition, lifestyle changes, and environmental degradation. Nevertheless, the Sanro Pammana continues to persist and demonstrate a capacity for adaptation amid changing times, indicating the importance of efforts to preserve and develop traditional healthcare practices as integral components of the cultural heritage and healthcare system of the Bugis People.